Frederick and his friends : four favorite fables - Lionni, Leo, 1910-1999. (New York : Alfred A. Knopf, 2002)
Four titles previously published independently, three of which were Caldecott honor books.
Frederick -- Fish is fish -- Alexander and the wind-up mouse -- Swimmy.
One sound disc (digital ; 4 3/4 in.) of word-for-word stories in back cover pocket.
Set of four titles previously published independently, three of which were "Caldecott honor book" winners.
Music by Blane and DeRosa Productions.
Keywords: Children's stories, American; Animals -- Fiction; Short stories